Functional characterisation of the small RNA Arp in Acinetobacter baumannii and the development of a programmable sRNA to modulate carbapenem resistance - Connell, Orla (Trinity College Dublin. School of Genetics & Microbiology. Discipline of Microbiology, 2026)
The World Health Organisation’s number one critical priority pathogen Acinetobacter baumannii (A. baumannii) is a Gram-negative bacterium which can cause multi-drug resistant infections, particularly pneumonia, bloodstream and wound infections. This bacterium has developed resistance to last-line antibiotics such as carbapenems, which calls for the discovery of new treatments and understanding these mechanisms of resistance. A. baumannii succeeds as a pathogen due to its persist and resist mechanisms, partially due to the plasticity of the bacterium’s genome. Bacterial regulatory small RNAs (sRNAs) are crucial for responding to the changing environment through the quick fine tuning of gene expression at a post transcriptional level. They can activate or repress the translation of certain genes via antisense base pairing in response to stressors in the environment, allowing for the bacteria’s survival. Until recently, the post-transcriptional landscape of multi-drug resistant A. baumannii had remained unclear. In this study, the sRNA Arp which was recently uncovered through Hi-GRIL-seq, was validated to bind the target mRNA pilA which is a major component in type IV pili in A. baumannii AB5075. Arp was then functionally characterised as a repressor of the type IV pili phenotypes twitching motility and DNA uptake. The second part of this study investigated the potential of an RNA based therapy to treat carbapenem resistant A. baumannii. Small regulatory RNAs have been used as a blueprint for the creation of RNA based antibiotics such as antisense oligonucleotides (ASOs). These antibiotics target essential genes in pathogenic bacteria, repressing the translation of genes involved in crucial pathways and killing the bacteria. This study used the new plasmid toolkit pAMCK to validate other known sRNA-mRNA interaction pairs in A. baumannii AB5075. One of the tested sRNAs Aar was chosen as a sRNA scaffold for the development of the programmable sRNA Aar-oxa23, which aimed to re-sensitise A. baumannii to already available carbapenem antibiotics. The sRNA has an altered seed region which targets and represses the translation of the carbapenem resistance gene Oxa-23 in A. baumannii. This proved to reduce the protein levels of Oxa-23 and therefore reduce A. baumannii’s resistance to the carbapenems imipenem and meropenem. These results highlight important insights into A. baumannii sRNA mediated regulation mechanisms, as well as advances in sRNA therapeutics, such that the alteration of the short seed region is sufficient to target and produce the desired effect on the target mRNA.
APPROVED